2016
DOI: 10.1016/j.biomaterials.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan thermogels for local expansion and delivery of tumor-specific T lymphocytes towards enhanced cancer immunotherapies

Abstract: Abstract:The success of promising anti-cancer adoptive cell therapies relies on the abilities of the perfused CD8 + T lymphocytes to gain access to and persist within the tumor microenvironment to carry out their cytotoxic functions. We propose a new method for their local delivery as a living concentrate, which may not only reduce the numbers of cells required for treatment but also enhance their site-specific mobilization. Using combinations of sodium hydrogen carbonate and phosphate buffer as gelling agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 53 publications
2
75
0
Order By: Relevance
“…How the pores present within the gel influence survival of encapsulated cells remains unclear and further investigation would be necessary to explain why some formulations are more favorable to cell growth, as observed here with fibroblasts and previously with entrapped T Lymphocytes. [24] Future in vivo studies will also investigate the biocompatibility of the hydrogels, as well as the survival and the phenotype of encapsulated cells, as insufficient diffusion of oxygen and nutrients within the scaffold in vivo could lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…How the pores present within the gel influence survival of encapsulated cells remains unclear and further investigation would be necessary to explain why some formulations are more favorable to cell growth, as observed here with fibroblasts and previously with entrapped T Lymphocytes. [24] Future in vivo studies will also investigate the biocompatibility of the hydrogels, as well as the survival and the phenotype of encapsulated cells, as insufficient diffusion of oxygen and nutrients within the scaffold in vivo could lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using a different type of thermosensitive chitosan-based hydrogels found that mechanical properties, gelation behaviour and porosity of the scaffold are highly important for T cell survival, ensuring cellular proliferation and dispersion. Importantly, gels containing pores of 50 to 500um in size optimally facilitated T cell escape towards the tumour, and maintained their ability to kill tumour cells 60 . Scaffold-based adoptive transfer of T cells was further explored by creating reservoirs of potent tumour-specific CTLs using macroporous alginate scaffolds decorated with adhesion peptides 61…”
Section: Scaffold-based Adoptive Cell Transfermentioning
confidence: 99%
“…Scaffolds may be pre-formed and delivered via implantation 58,61,63 , or formulated such that they are injectable and gelate in situ, for instance in response to temperature 59,60,62 or by addition of crosslinkers [55][56][57] . Minimal invasive delivery through injection is highly favourable, although pre-formed scaffolds enable more control over mechanical structure and localization of the scaffold, and prevent leakage of injected scaffold into the environment as might be the case for in situ gelating systems 71 .…”
Section: Box 1 Tools To Engineer Synthetic Immune Nichesmentioning
confidence: 99%
“…Here, hydrogel scaffolds serve as a barrier to isolate implanted cells from the immune system, preventing immune-rejection 4 while allowing bidirectional diffusion of oxygen, nutrients, and cell products and wastes 5 . Advances in hydrogel scaffold development has facilitated cell encapsul ation as a potential therapy for type 1 diabetes 6 , cartilage 7 and bone regeneration 8 , osteroarthritis 9 , Parkinsonian symptoms 10 and cancer 11 . A variety of cell encapsulants have been investigated including agarose 12 , alginate 13 , collagen 14 , and hyaluronic acid 15 .…”
Section: Introductionmentioning
confidence: 99%